Positive Emotion Regulations Among English as a Foreign Language Teachers During COVID-19 - Zhao, Hongdan (Frontiers in Psychology, 2021)
As the cores of education, teachers’ emotions have a critical place in academia. However, the power of EFL (English as a foreign language) teachers’ positive emotions and their regulation in online mode of instruction have been ignored by scholars. With the rapid shift of education from face-to-face to remote/electronic delivery, many challenges and emotional problems emerged among teachers and learners worldwide. This entailed the necessity of considering and planning for emotional regulation to generate positive outcomes. To provide a roadmap for this line of research, the present mini-review article presented the theoretical and empirical underpinnings of emotion regulation, its origins and definitions, as well as outcomes for second/foreign language education. The study also presents some implications for EFL teachers, teacher trainers, and avid scholars of this area of research pinpointing the current yawning gaps.